Physico-chemical applications of NMR : a practical guide - Kudryavtsev, A. B.; Linert, W.; World Scientific (Firm) (Singapore ; River Edge, N.J. : World Scientific Pub. Co., 1996)
The book is intended to help under- and postgraduate students and young scientists in the correct application of NMR to the solution of physico-chemical problems concerning the study of equilibria in solution. The first part of the book (Chapters 1-3) is a trivium, but should enable a student to design and conduct simple physico-chemical NMR experiments. The following chapters give illustrative material on the physico-chemical applications of NMR of increasing complexity. These chapters include the problem of determination of equilibrium and rate constants in solution, the study of paramagnetism using NMR, the application of Dynamic NMR techniques and relaxation measurements. A multipurpose nonlinear regression program is supplied (on disc for PC) and is referred to throughout the book.
ch. 1. NMR - Basic principles. 1.1. The phenomenon of nuclear magnetic resonance. 1.2. NMR spectra and their parameters. 1.3. Simplification of NMR spectra. 1.4. Analysis of NMR spectra. 1.5. Some hints on the mechanisms of relaxation and the nuclear Overhauser effect. 1.6. Physico-chemical aspects of the NMR. 1.7. Conclusion to chapter 1 -- ch. 2. Experimental techniques employed in NMR. 2.1. Introduction. 2.2. Principles of Fourier transform NMR spectroscopy. 2.3. Special features of the physico-chemical NMR experimental technique. 2.4. Routine of a typical PMR analysis of an organic compound -- ch. 3. The analysis of experimental data by regression techniques. 3.2. Introduction. 3.3. Definitions. 3.3. Least square fitting. 3.4. Non-linear least square methods -- ch. 4. Studies of equilibria in the liquid state by NMR spectroscopy. 4.2. Introduction. 4.2. Equilibria with slow exchange. 4.3. Equilibria with fast exchange -- ch. 5. Studies of paramagnetism in solutions by NMR. 5.1. Magnetochemistry. 5.2. Contact shifts -- ch. 6. Dynamic NMR and nuclear magnetic relaxation measurements. 6.1. Dynamic NMR. 6.2. Relaxation measurements.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Nuclear magnetic resonance spectroscopy; Electronic books